Introduction of Indonesia's Halal Industry to the Filipino Society - Dura, Justita; Cahyaningtyas, Fadilla; Indahsari, Rina Dewi; Aqromi , Nur Lailatul; Afiyah, Siti Nurul; Setyorini, Setyorini; Arifin, Samsul; Kurniawan, Karolus Danar; Kurniawan, Hironimus Hari; Kala'lembang, Adriani (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This research aims to introduce and educate the Filipino people about the Indonesian halal industry. Method: Educational programs are carried out through seminars, workshops and consultation sessions. The seminar provides theoretical knowledge about the concept and importance of halal products. Practical Applications:Filipinos will have a better understanding of halal products and their importance, so they can make more informed choices. Entrepreneurs in the Philippines will be equipped with the knowledge and skills to develop products that meet international halal standards. Increasing cooperation between Indonesia and the Philippines in the halal industry, strengthening bilateral and economic relations between the two countries. Conclusion:This educational program succeeded in increasing awareness and knowledge about the Indonesian halal industry among the Filipino people. This program provides practical guidance for entrepreneurs in developing halal products, contributes to the growth of the halal market in the Philippines, and strengthens bilateral relations between Indonesia and the Philippines